Psychological distress in relation to blood pressure among Andhra Pradesh state road transport corporation bus drivers, Vijayawada - Y., Mary Chaitanya; Harish K.; J., Bharani Parasuram; Amarnath M.; Ravikumar J. (International Journal Of Community Medicine And Public Health, 2023)
Background: One of the major health problem worldwide is elevated blood pressure (BP). Prior research had shown that hypertensives experience psychological distress, although pre-hypertensives have not yet been subject to this research. Objectives were to assess the major risk factors of increasing BP among bus drivers and to assess psychological distress in relation to BP levels. Methods: A cross sectional study was conducted among Bus drivers aged above 20 years, study was carried out between July to October of 2022, a sample of 135 was taken. Inferential statistics such as Pearson Chi square test and an unpaired independent-sample t-test was used to assess the difference between pre-hypertensive and hypertensive individuals on GHQ score. Results: In the present study (n=135), 47% were normotensive, 34% were in hypertensive stage and 19% were in pre-hypertensive stage. On assessment of psychological distress in relation to BP among bus drivers the mean of (General health questionnaire) GHQ-12 was found to be 17.57 among hypertensives and 17.86 among pre-hypertensives. Two tailed significance value of 0.768 was observed between pre-hypertensive and hypertensive individuals indicating that psychological distress had significant effects. Conclusions: The prevalence of hypertension and pre-hypertension was among bus drivers, leading to cardio vascular diseases which in turn causes increased morbidity and mortality, lowering individual productivity and having an impact on the national economy. The prevalence of non-communicable diseases should be monitored by lifestyle changes and periodic screenings.